The Effects of Solution Chemistry on the Transport, Retention and Dissolution of Silver Nanoparticles in Water-Saturated Sand. - Mittelman, Anjuliee. (2017)
Abstract: Silver nanoparticles (nAg) are widely used as antimicrobial agents in medical and consumer products and represent a potential threat to natural environments. This research was designed to assess the effect of solution chemistry on the fate and transport of nAg in groundwater systems. The effects of pH, ionic strength and dissolved oxygen (DO) on nAg transport, retention and dissolution kinetics in water-saturated sands were evaluated through a series of batch, one-dimensional column and two-dimensional aquifer cell studies. The mobility and dissolution of nAg in sand columns were found to be a strong function of solution chemistry; deposition increased with decreasing pH, increasing ionic strength and increasing DO. In batch and column studies, dissolution was enhanced at lower pH values and higher DO concentrations. Results from column and aquifer cell studies indicate that nAg retained in porous media can serve as long term sources of silver ion.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Civil Engineering.; Advisor: Kurt Pennell.; Committee: Linda Abriola, and Yusong Li.; Keyword: Environmental engineering.